Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3329/ajmbr.v3i3.34529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth performance between monosex and natural XY male tilapia in Noakhali region, Bangladesh

Abstract: Abstract:The study was conducted to compare the growth and production performance of monosex and natural XY male tilapia of Oreochromis niloticus in Bismillah Agro production hatchery of Noakhali Sadar in Noakhali district, Bangladesh from September to November, 2014. The length, weight, average FCR value, Average SGR value, Daily weight gain, survival rate of fish were observed. Relationship between growth and physicochemical parameter of water were also investigated for monosex and XY male tilapia. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
9
2
0
Order By: Relevance
“…At higher stocking densities, presence of abundant feed substance could produce a competitive interaction among the larvae causing a stressful situation (Houde, 1975). Similar results were observed by Rahman et al (2017b) and Haq et al (2017). In the present experiment the average survival rate of Vietnamese koi and Magur were found at the end of the experiment which were 95.14% and 72% in T 1 ; 93.25% and 64% in T 2 ; 90.80% and 68.00% in T 3 respectively.…”
Section: Benefit-cost-ratio (Bcr)supporting
confidence: 84%
“…At higher stocking densities, presence of abundant feed substance could produce a competitive interaction among the larvae causing a stressful situation (Houde, 1975). Similar results were observed by Rahman et al (2017b) and Haq et al (2017). In the present experiment the average survival rate of Vietnamese koi and Magur were found at the end of the experiment which were 95.14% and 72% in T 1 ; 93.25% and 64% in T 2 ; 90.80% and 68.00% in T 3 respectively.…”
Section: Benefit-cost-ratio (Bcr)supporting
confidence: 84%
“…Kujawa (2004), Kwiatkowski et al (2008), recorded crucian carp body weight ranged 1.3 to 3.0 mg. Rcma and Gouveia (2005) recorded 0.9 mg of wet body weight of fish. Similar study was conducted by Samad et al (2016); Islam et al (2017); Rahman et al (2017); Rahman et al (2016); Anka et al (2016); Ali et al (2016); Zaman et al (2017) and Haq et al (2017); they got relevant results. It was observed that the highest weight gain of gold fish fry was obtained from anent T 1 which might be due to lower stocking density and lower competition for lowest weight gain was obtained from T 3 which might be due to comparatively her stocking density so the feeding competition may occur among the species.…”
Section: Discussionsupporting
confidence: 64%
“…The results indicated that the percent weight gained in different stocking densities which coincides with the findings of Begum (2009) found percent weight gain ranged from 7986 to 9406%. Study of Ali et al (2016); Zaman et al (2017) and Haq et al (2017) was also relevant with present study.The percent weight gain of present study was lower than findings; this might be due to the temperature difference between regions and natural productivity of the ponds. The other reason might be due to the difference of culture season.…”
Section: Discussionsupporting
confidence: 59%
“…Malla and Banik (2015)reported that SGR of Ompak bimaculatus was 4.79±0.58 to 3.46±0.31 that is similar with the present study. Similar phenomena were also observed in other fish species, for instance, tilapia (Haq et al, 2017). The highest survivability was recorded in treatment T 2 (96.77 ±0.01) and the lowest survivability was in treatment T 1 (90.43 ±0.01).…”
Section: Discussionsupporting
confidence: 86%